2010
DOI: 10.1627/jpi.53.327
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Dehydrogenation of Ethane over NiO-loaded High Surface Area ZrO<sub>2</sub> Catalysts

Abstract: The oxidative dehydrogenation of ethane (ODHE) over POn/NiO/ZrO2 (High Surface area Zirconia: HSZ) catalyst was carried out with a fix-bed flow reactor at 450 under atmospheric pressure. The ODHE without dilution of reactants with inert gas resulted in ethane conversion of 32.1%, with a high ethene selectivity of 64.2% and an ethene yield of 20.6%. In addition, the catalytic activity did not decrease for at least 12 h. In XPS analysis, Ni species of NiO/HSZ catalyst after the reaction exhibited partly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…41,42 Finally, it should be noted that adding phosphorus to a high surface area zirconia-supported NiO catalyst increased both its catalytic activity and ethylene selectivity in ethane ODH. 30 The presence of phosphorus enabled the Ni species to remain in an oxidized state during the ODH reaction, i.e. it was not reduced to metallic Ni, as observed for the unpromoted catalyst.…”
Section: Introductionmentioning
confidence: 90%
“…41,42 Finally, it should be noted that adding phosphorus to a high surface area zirconia-supported NiO catalyst increased both its catalytic activity and ethylene selectivity in ethane ODH. 30 The presence of phosphorus enabled the Ni species to remain in an oxidized state during the ODH reaction, i.e. it was not reduced to metallic Ni, as observed for the unpromoted catalyst.…”
Section: Introductionmentioning
confidence: 90%
“…NiO is known to be very reactive and capable of activating ethane at moderate temperature (below 400°C) [13,14]. Furthermore, the physical and chemical properties of NiO can be modified and improved by doping with transition metals, such as Nb [15][16][17][18][19][20], Zr [21,22], W [23], the main group element Sn [24] or by supporting it on SiO 2 , Al 2 O 3 , ZrO 2 , and MgO [25][26][27][28][29]. The resulting NiO based materials deliver increased ethylene yield.…”
Section: Introductionmentioning
confidence: 99%
“…Takita et al have reported that Ni 2 P 2 O 7 exhibits high selectivity in the ODH of iso-butane to iso-butene [34]. We have found that PO x / NiO/ZrO 2 having a high surface area exhibits a high ethane conversion with high ethylene selectivity in the ODHE [35]. Runs 12-14 show the effects of additives to NiO-ZrO 2 (c) on the ODHP.…”
Section: Effect Of Various Additives To Nio-zro 2 (C) On the Odhpmentioning
confidence: 70%